Human agency and instrumental rationality: applying human capital to gender inequalities and intergenerational stratification - Luo, H (2023)
Background and Motivation Existing literature highlights education's potential for reducing inequalities and fostering social mobility. However, our understanding of its precise role remains incomplete. This thesis contends that educational attainment, a form of human capital, can evolve differently based on human agency and instrumental rationality, influencing its effectiveness in mitigating inequalities and enhancing mobilities.